Gendered Request Strategies Used by Bugis EFL Teachers in Indonesian Classrooms: A Sociocultural Study - Nurul Hasanah; Yessicka Noviasmy; Rahma Melati Amir; Nanning; Syahban Mada Ali (STAIN Majene, 2026)
This study examines gendered request strategies in Indonesian EFL classrooms from a sociocultural perspective, focusing on how Bugis EFL teachers negotiate authority, politeness, and interpersonal relations through classroom requests. Drawing on sociocultural approaches to classroom discourse and pragmatics, the study investigates how local cultural norms shape teachers’ interactional practices during English-mediated instruction. Employing a qualitative discourse-analytic design, data were collected through classroom observations, audio recordings, and semi-structured interviews involving four Bugis EFL teachers at a senior high school in South Sulawesi, Indonesia. A total of 360 minutes of naturally occurring classroom interaction were transcribed and analyzed thematically. The findings reveal distinct gendered patterns in classroom request realization. Female teachers tended to employ mitigated and relationally oriented requests through modalization, hedging devices, minimizers, and kinship-based address terms to maintain interpersonal rapport and participation. In contrast, male teachers tended to employ more direct and task-oriented request strategies emphasizing instructional clarity, efficiency, and classroom control. The findings further demonstrate that classroom requests function not merely as pedagogical directives but as socioculturally mediated interactional practices shaped by local sociocultural understandings of hierarchy, solidarity, and politeness within the Bugis cultural context. This study contributes to sociocultural approaches to classroom pragmatics by highlighting the importance of localized cultural meanings in interpreting classroom discourse and gendered communication in multilingual EFL settings.